Music and Sound in (Exer)Games - Wiemeyer, J. (International Journal of Computer Science in Sport, 2013)
Music plays in important role in human culture. This is also the case for exercise, games and exergames. In this study we examine the influence of previous game experience and the presence of music and sound on game performance and game experience. Sixteen students (12 males, 4 females; age: M = 24.8 years, SD = 3.4) played two exergames with and without sound and music. Game performance, game experience and the perception of sound and music were assessed as dependent variables. Whereas music and sound had no impact on game performance, selected dimensions of game experience (tension, positive affects) were significantly influenced. The game-specific significance of music and sound was confirmed by the participants.